Assessment of reflection-based education on reflective thinking skills of dental students: A quasi experimental study - Maryam Kazemipoor; Fatemeh Keshmiri (Zanjan University of Medical Sciences and Health Services, 2023)
Background & Objective: Reflection plays an important role in the students' learning. The present study aimed to assess the effect of reflection-based education on the thinking skills and performance of dental students. Materials & Methods: This is a quasi-experimental study. A total of 34 dental students that passed basic science courses and entered the clinical departments have participated. Educational interventions based on Gibbs' reflection model were conducted through educational workshops and workplace-based education. The reflective thinking of students was assessed by a 16-item questionnaire in four domains of habitual performance, understanding, reflection, and critical reflection. The students' performances were assessed by an observational examination. Data were analyzed by descriptive and analytical tests in SPSS ver.17. The significance level was P-value≤ 0.05. Results: The students' score of reflective thinking before the educational intervention was 14.48±2.73 and after the training was 15.35±1.33. There were significant differences in the scores of the reflection domain before and after educational interventions. (p-value=0.01). The learning scores of students were reported 17.56 that significantly higher than the minimum pass level. (P-value=0.01). Conclusion: Reflection-based education decreases the level of habitual performance and increases reflection among dental students. Therefore, it is recommended that reflection as a main component of clinical education throughout the practical courses be considered in dental schools.